Water adsorption at zirconia: from the ZrO2(111)/Pt3Zr(0001) model system to powder samples. Issue 36 (31st August 2018) - Lackner, Peter; Hulva, Jan; Köck, Eva-Maria; Mayr-Schmölzer, Wernfried; Choi, Joong Il J.; Penner, Simon; Diebold, Ulrike; Mittendorfer, Florian; Redinger, Josef; Klötzer, Bernhard; Parkinson, Gareth S.; Schmid, Michael
Abstract : A comprehensive study of water adsorption and desorption on an ultrathin trilayer zirconia film by experimental and computational methods shows good agreement with data for H2 O/ZrO2 powder material. Abstract : We present a comprehensive study of water adsorption and desorption on an ultrathin trilayer zirconia film using temperature programmed desorption (TPD), X-ray photoelectron spectroscopy (XPS), as well as scanning tunneling microscopy (STM) at different temperatures. The saturation coverage is one H2 O per surface Zr atom, with about 12% dissociation. The monolayer TPD peak (180 K, desorption barrier 0.57 ± 0.04 eV) has a tail towards higher temperatures, caused by recombinative desorption from defect sites with dissociated water. STM shows that the defects with the strongest H2 O adsorption are found above subsurface dislocations. Additional defect sites are created by multiple water adsorption/desorption cycles; these water-induced changes were also probed by CO2 TPD. Nevertheless, the defect density is much smaller than in previous studies of H2 O/ZrO2 . To validate our model system, transmission Fourier-transform infrared absorption spectroscopy (FTIR) studies at near-ambient pressures were carried out on monoclinic zirconia powder, showing comparable adsorption energies as TPD on the ultrathin film. The results are also compared with density functional theory (DFT) calculations, which suggest that sites with strong H2 O adsorption contain twofold-coordinated oxygen.